(untitled) (Pulse, 2024)
Surgical Site Infection (SSI) is an infection that occurs after any surgical procedure with adverse effects on a patient’s prognosis. SSIs are caused by a variety of bacteria including Non-Tuberculous Mycobacteria (NTM). Nowadays, NTM is reported as an important pathogen in delayed healing of surgical site infections in post-operative cases in many countries, however, there is no report yet in the country due to lacking any sensitive detection method. By multiplex PCR we previously reported the existence of NTM in a variety of clinical specimens and here we report NTM in SSI. Out of 98 patients with SSI, the total NTM positive cases were 20(20.4%) and Mycobacterium Tuberculosis (MTB) was 6(6.1%). NTM positivity rate was higher in female 13(65%) than male 7(35%). The majority (13) of the patients were treated with a combination of Clarithromycin and Ciprofloxacin with or without the first line of Anti-Tubercular Therapy (ATT) and cured. In the case of patients with delayed recovery of SSI, there should be a high level of clinical suspicion for the NTM as a causative agent and Multiplex PCR can be utilized to diagnose NTM and to discriminate from MTB. Pulse Vol.15, 2023 P: 22-27